Effect of sex and time to slaughter (transportation and lairage duration) on the levels of cortisol, creatine kinase and subsequent relationship with pork quality. (June 2016) - Jama, N.; Maphosa, V.; Hoffman, L.C.; Muchenje, V.
Abstract: The study determined the effect of sex and time to slaughter on cortisol and creatine kinase levels, and pork quality in commercial crossbred pigs. Saliva samples were before collected transportation, on arrival at the abattoir, and after a 20 hour lairage period. Cortisol levels from saliva (SC), serum (SeC) and urine (UC) were determined. Creatine kinase (CK) levels were determined from serum samples. Fifteen boars vs. 15 gilts were immediately slaughtered on arrival (SOA), and the other 15 boars vs. 15 gilts were rested for 20 h before slaughter. Meat quality parameters were also determined. In both sexes, SC significantly increased in response to time to slaughter. There was a significant interaction of sex and time to slaughter on SeC. Gilts had higher CK levels and lower muscle L* values than boars. There were correlations among baseline SC, SeC, UC and most meat quality parameters. Time to slaughter influenced levels of SC, UC, CK and pork quality between boars and gilts. Highlights: Relationships between saliva, urine and serum cortisol levels and pork quality were determined. Pre-slaughter and sex effects on cortisol, creatine kinase response and pork quality were found. A gender by lairage interaction was found for serum cortisol and meat cooking loss. Saliva cortisol correlated strongly with urine and serum cortisol and meat quality traits.